PROSES MODEL PENJADWALAN PROYEK DENGAN ALGORITME GENETIKA - Adnyana Putera, I Gusti Agung (Jurnal Ilmiah Teknik Sipil, 2012)
In the real construction world, resources for construction activities are usually limited. The critical path method (CPM) that has been intensively used in construction industry for planning and controlling of construction, is not feasible for this problem because of the unlimited resources assumption. To deal with the limited resources, construction planner must include resources allocation in order to find out an applicable project planning. The activity’s duration and their sequences may need to be adjusted by considering the available resources at the considered time. This paper presents a process model for project planning using the genetic algorithm searching technique to solve the multicriteria problem in construction planning in order to find out an optimal construction project planning. The genetic algorithm can solve the combinatorial problems of project planning and give an integrated planning solution, such as, project planning, resources levelling, smoothing by considering multi-criteria and multi-constraints for project planning.
Keywords: Genetic algorithms, project planning and scheduling, process model, optimisation.